Effectiveness of Internal Control, Employee Competence, Information Technology on Fraud Tendency in Sales Accounting System - Rahayu, Ni Nyoman Saras Tri; Animah, Animah (E-Jurnal Akuntansi; Vol 35 No 5 (2025), 2025)
The purpose of this study is to analyze the effect of internal control effectiveness, employee competence, and information technology on the tendency of fraud in the sales accounting system at gas stations. Data were collected from 236 respondents who work at various gas stations in Mataram City. The data analysis technique used Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of the study show that the effectiveness of internal control and employee competence have a significant effect in reducing the tendency of fraud. The stronger the control system and the higher the employee competence, the less likely fraud is to occur. However, information technology does not significantly affect the tendency of fraud, which indicates that the application of technology needs to be balanced with a tighter supervision system. This study provides implications that reducing fraud in the sales accounting system at gas stations can be achieved by strengthening internal control and increasing employee competence , while the implementation of information technology requires strict supervision because it does not automatically reduce fraud. Keywords : Internal Control, Employee Competence, Information Technology, Accounting Fraud, Sales Accounting System, Gas Station.